Make a Move+: A Cluster-Randomized Controlled Trial of a Program Targeting Psychosexual Health and Sexual and Dating Violence for Dutch Male Youth with Mild Intellectual Disabilities - Mirthe C. Verbeek; Daphne van de Bongardt; Maartje P. C. M. Luijk; Elizabeth Miller; Eric A. W. Slob; Joyce Weeland (Youth, 2025)
While male youths with mild intellectual disabilities (MIDs) display similar sexual development as their peers without MIDs, they experience higher rates of sexual and dating violence (SDV) and sexual risk behavior. Yet, little is known about effective gender-specific prevention for this population. Therefore, we conducted a cluster-randomized controlled trial of a Dutch group-counseling program promoting psychosexual health and preventing SDV among male youths with MIDs aged 14–21 years—Make a Move+. The 120 participating male youths completed three questionnaires (baseline, post-test, 3-month follow-up; 77.5% retention). A subsample of 14 male youths and 5 trainers were interviewed pre- and post-program. With these multi-method, multi-informant data, we evaluated the program’s effectiveness on the six intended outcomes (attitudes (primary outcome), global self-esteem, skills, knowledge, SDV use and victimization, and sexual risk behavior) by (1) statistically comparing the self-reports of the intervention and control groups and (2) thematically analyzing interview data. We found limitations in the program’s integrity, and mixed evidence for the program’s effectiveness on attitudes, knowledge, skills, SDV use, and sexual risk behavior, and no evidence for effectiveness on global self-esteem or SDV victimization. We also found indications of adverse effects on SDV use and victimization. We offer suggestions for program refinement and future program evaluations.